(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
The Ulziit Mountain has a unique ecosystem which is one of northern branch mountains of Khangai mountain range in Mongolia. Several field survey were conducted in summer in all habitats in different altitudes. A total of 314 taxa were registered belonging to 161 genera from 52 families in Ulziit Mountain flora. The family Asteraceae was found to be the largest with 37 taxa, followed by Poaceae with 30 taxa, Ranunculaceae with 24 taxa, Cyperaceae, Caryophyllaceae and Rosaceae each with 17 taxa, Salicaceae with 16 taxa, and Fabaceae with 15 taxa; in total, these comprised 55.1% of all flora complements in this mountain. During the investigation, 5 species were newly recorded in the Khangai mountains forest-steppe region. The most represented life forms in the flora are hemicryptophytes (71.97%), which are common for mountain steppe vegetation. In a time of climate change, effective conservation of nature is needed at an ecosystem such as a single mountain particularly for endemic, relict and other salient species. Furthermore, such a detailed floristic survey is important for finding new records in the field of plant taxonomy and conservation of nature in these specific areas. Bangladesh J. Plant Taxon. 28(1): 195-215, 2021 (June)